ОРЧИН ҮЕИЙН УЛС ТӨРИЙН НАМЫН ХӨГЖЛИЙН ХАНДЛАГА: ПАРТИЗАНЫ УЛС ТӨРӨӨС АЛЬТЕРНАТИВ КОММУНИКАЦИ ТИЙШ - Ж.ТӨРТОГТОХ (Politology, 2023)
In this article, contemporary political party development tendencies are reviewed. First of all, nowadays research methodologies on political party are considered. Then the paper divided by the parts as partisan politics, non-partisan politics, institutional development of political party, a basis of mature democracy, party as an alternative institutional form of political communication as well as a bridge between public and government. As concluding remarks, further research discussions are put in frame of how to institutionalize political parties.